Technology of organizing the training process of highly qualified handball players (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the key aspects of organizing an effective training process for high-level handball players. It covers modern training methods, periodization, physical and tactical preparation, as well as psychological aspects to enhance performance.